On the Need for Methods Beyond Proceduralism: Speculative Middles, (In)Tensions, and Response-Ability in Research. (March 2018) - Springgay, Stephanie; Truman, Sarah E.
This article responds to agitations occurring in qualitative research related to the incompatability between methodologies and methods, the preponderance of methodocentrism, the pre-supposition of methods, a reliance on data modeled on knowability and visibility, the ongoing emplacement of settler futurity, and the dilemma of representation. Enmeshments between ontological thought and qualitative research methodologies have rigorously interrogated the logic of anthropocentrism in conventional humanist research methods and have provoked some scholars to suggest that we can do away with method. Rather than a refusal of methods, we propose that particular (in)tensions need to be immanent to whatever method is used. If the intent of inquiry is to create a different world, to ask what kinds of futures are imaginable, then (in)tensions need attend to the immersion, friction, strain, and quivering unease of doing research differently.